POTRET KINERJA DAN PELAYANAN PUBLIK OLEH PEMBANTU PEGAWAI PENCATAT NIKAH (P3N) DI KABUPATEN TANGERANG: KASUS KUA KECAMATAN CIKUPA, CURUG, TELUK NAGA, DAN KOSAMBI: PORTRAITS OF PERFORMANCE AND PUBLIC SERVICE BY THE ASSISTANT MARRIAGE REGISTRARS (P3N) IN TANGERANG REGENCY: A CASE STUDY OF RELIGIOUS AFFAIRS OFFICES (KUA) SUB-DISTRICT CIKUPA, CURUG, TELUK NAGA, AND KOSAMBI - ismail ismail (Penamas, 2015)
Researches on the existence of the assistant marriage registrars have been done by many researchers, academics and students. However, only few studies on performance and public services. This paper presents performance and public service performed by the assistant marriage registrars in Tangerang Regency. Tangerang Regency is one of the regions in Banten province, which has many assistant marriage registrars. After the issuance of Letter of Instruction No.DJ. II/113/2009 on the Use of Funds Non-Tax State Revenue (PNPB) on Marriage and Reconciliation and Structuring the Assistant Marriage Registrars (P3N), then the existence of the assistant marriage registrars is not extended. However, community still uses services from the Assistant Marriage Registrars, which has already renamed with â€œamilâ€. This study used qualitative methods of interview, study of documents, and observation. The study concluded that the presence of the assistant marriage registrars in Tangerang district is still required. Their performances are quite good, but services they provided have not met the standards for public service. Their unclear salaries become one of the barriers faced by the assistant marriage registrars. Yet, there is a lot of public confidence in them, which makes the barrier disappear. This leads to increase their motivation, and create conducive and harmonious their working climate.Keywords: Public services, marriage registrars, religious public services, Tangerang-Banten. Penelitian tentang eksistensi Pembantu Pegawai Pencatat Nikah (P3N) sudah banyak dilakukan oleh para peneliti, akademisi maupun mahasiswa. Tapi yang meneliti tentang kinerja dan pelayanan publik belum banyak dilakukan. Tulisan ini memotret kinerja dan pelayanan publik yang dilakukan oleh Pembantu Pegawai Pencatat Nikah (P3N) di Kabupaten Tangerang. Kabupaten Tangerang adalah salah satu wilayah di Provinsi Banten yang memiliki banyak P3N. Setelah keluarnya Surat Instruksi No.DJ.II/113/2009 tentang Penggunaan Dana PNPB Nikah dan Rujuk dan Penataan Pembantu Pegawai Pencatat Nikah (P3N), maka keberadaan P3N tidak diperpanjang lagi masa tugasnya, namun masyarakat tetap menggunakan jasa P3N yang sudah berganti nama dengan amil. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif dengan menggunakan teknik wawancara, studi dokumen, dan observasi. Penelitian ini menyimpulkan, bahwa keberadaan P3N di Kabupaten Tangerang masih dibutuhkan, kinerjanya sudah cukup baik, namun pelayanan yang diberikan belum memenuhi standar pelayanan publik. Sedangkan honorarium yang belum jelas menjadi salah satu hambatan yang dihadapi oleh P3N, namun hal tersebut ditutupi dengan kepercayaan masyarakat yang masih besar terhadap mereka, sehingga menimbulkan motivasi, iklim kerja yang kondusif dan harmonis.Kata Kunci: Pelayanan publik, pencatatan nikah, pelayanan publik keagamaan, Tangerang, Banten.